ANOVA-Based Evaluation of Radium, Thorium, and Potassium Levels in Soil Samples of Rajpur Region, Dehradun District, Uttarakhand, India - Sharan, Ganga; Upadhyaya, Lalit Mohan; Aggarwal, Sudhanshu (Journal of Advanced Research in Geo Sciences & Remote Sensing, 2025)
Based on a recent study on radionuclide concentrations in soils by Tushar Kandari et al. (Journal of Radioanalytical and Nuclear Chemistry, 2021, 330:1545–1557, https://doi.org/10.1007/s10967-021-07988 2), we analyze the average concentrations of Radium-226 (²²⁶Ra), Thorium-232 (²³²Th), and Potassium-40 (⁴⁰K) in the soil samples from the Rajpur region of Dehradun district, Uttarakhand, India. Our analysis employs a one-way repeated measures ANOVA model technique to evaluate the concentrations of these radionuclides.